2012
DOI: 10.1093/eurheartj/ehr505
|View full text |Cite
|
Sign up to set email alerts
|

Sites of left and right ventricular lead implantation and response to cardiac resynchronization therapy observations from the REVERSE trial

Abstract: A more favourable outcome of CRT with regard to LV reverse remodelling and the composite of time to death or first HF hospitalization was observed when the LV lead tip was implanted in the lateral wall, away from the apex, while the position of the RV lead tip was indifferent. The long-term change in QRS duration was significantly associated with the position of the LV lead tip. ClinicalTrials.gov Identifier: NCT00271154.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 33 publications
7
119
0
8
Order By: Relevance
“…The cause and mode of death were not considered in either MADIT‐CRT2 or REVERSE 3. Our finding of lower cardiac mortality as well as death from pump failure with an apical LV lead position is in keeping with experimental and clinical studies showing that LV apical pacing is physiologically superior to nonapical pacing 4, 5…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The cause and mode of death were not considered in either MADIT‐CRT2 or REVERSE 3. Our finding of lower cardiac mortality as well as death from pump failure with an apical LV lead position is in keeping with experimental and clinical studies showing that LV apical pacing is physiologically superior to nonapical pacing 4, 5…”
Section: Discussionsupporting
confidence: 66%
“…A subanalysis of the MADIT‐CRT (Multicenter Automatic Defibrillator Implantation Trial–Cardiac Resynchronization Therapy) trial, apical LV lead positions were less favorable than basal or mid‐LV lead positions in terms of total mortality and HF hospitalization 2. Similar findings emerged from a subanalysis of the REVERSE (Resynchronization Reverses Remodeling in Systolic Left Ventricular Dysfunction) trial 3. These findings are counterintuitive, as previous experimental and clinical evidence shows that an apical LV lead position is more favorable than nonapical positions 4, 5.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Subanalysis of MADIT‐CRT21 demonstrated that the apical position of left ventricular lead was associated with worse outcome. Similar result was confirmed in the subanalysis of REVERSE trial 22. To reduce the number of patients who do not respond for CRT, the operator should avoid apical LV lead position as possible.…”
Section: How To Reduce Nonresponder? Importance Of Appropriate LV Pacsupporting
confidence: 74%